Pengungkapan Enterprise Risk Management dan Nilai Perusahaan: Peran Moderasi Umur dan Ukuran Perusahaan - Anggreni, Ni Kadek Ayu Asri; Suprasto, Herkulanus Bambang; Ariyanto, Dodik; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2021)
The purpose of the study was to obtain empirical evidence regarding the effect of enterprise risk management (ERM) disclosure on firm value with the role of age and firm size as moderating. The sampling technique used is purposive sampling technique. The data used in this study is secondary data obtained from the annual reports of insurance companies and financial institutions listed on the Indonesia Stock Exchange for the 2018-2019 period. The data analysis technique used moderated regression analysis (MRA). The results of the analysis show that ERM disclosure has a significant negative effect on the firm value of financing and insurance institutions. Firm age weakens the effect of ERM disclosure on firm value with a quasi moderator type of moderation. Firm size is not proven to moderate the effect of ERM disclosure on firm value and is a moderating predictor. Keywords : Firm Value; Enterprise Risk Management Disclosure;, Company Age; Company Size.